A GENERAL COMPUTATIONAL METHOD FOR MASS-TRANSPORT PROBLEMS INVOLVING WALL JET ELECTRODES AND ITS APPLICATION TO SIMPLE ELECTRON-TRANSFER, ECE AND DISP1 REACTIONS - Compton, R; Greaves, C; Waller, A (Kluwer Academic Publishers, 1990)
A computational procedure based on the Backwards Implicit Method is shown to be a powerful and general method of solving problems of mass transport to a wall-jet electrode. Conventional numerical methods based on a Cartesian grid are unsatisfactory because the electrode is very non-uniformly accessible. An expanding grid which increases in size in proportion to the diffusion layer thickness across the electrode surface, is shown to be effective in computing the limiting current-flow rate behaviour of (a) a simple electron-transfer reaction, (b) ECE, and (c) DISP1 processes. © 1990 Chapman and Hall Ltd.